The relationship between risk disclosure, risk management and firm performance - case of the Nairobi Securities Exchange Companies - Mwakima, Eddah (Strathmore University, 2014)
The subject of risk, risk disclosure and risk management has been getting more attention over the years. Due to globalization, firms are more prone to risks affecting business operations and decisions made by stakeholders. After the Enron and WorldCom scandals and the recent global financial crisis, for example, the world has become more aware of the importance of full disclosures and risk management as part of good practice in firms today. These and other factors have made the study of risk and its disclosure and management relevant today. This study explores the relationship between risk disclosure, risk management and firm performance in companies listed on the Nairobi Securities exchange. The objectives of this study are firstly to determine the risks disclosed and the extent of their disclosure in companies listed in the stock exchange; secondly to determine the extent of application of risk management practices in companies listed in the Nairobi Securities Exchange and lastly to investigate the relationship between risk disclosure, risk management and firm performance. In this paper, the extent of disclosure of risk was determined and scored against a predetermined set of attributes. The extent of risk management in companies listed on the NSE was also determined and scored against a predetermined set of attributes. A relationship between the above and the company's share price, net profit, return on equity and return on assets was then be established. Questionnaires were sent out to complement the study by gathering information on what the management input as far as risk disclosure and risk management is concerned. A simple regression technique was used to investigate the relationship. The results revealed that there does not exists sufficient evidence to support the existence of a relationship between risk disclosure, risk management and firm performance in companies listed on the Nairobi Securities Exchange. This is despite the general opinion of managers that risk disclosure and risk management affect firm performance. This also goes against empirical evidence that support the existence of a relationship between risk disclosure, risk management and firm performance.
A Research Proposal submitted in Partial fulfilment for the award of Bachelor of Business Science: Financial Economics degree
Keywords: Risk disclosure; Risk management; Firm performance; Nairobi Securities Exchange companies